PERANCANGAN MASKOT 3D SEBAGAI UPAYA PENGUATAN IDENTITAS VISUAL PEUSAHAAN GARMENT “BINTANG PERMATA SEJATI” DI KOTA PASURUAN - Glory, Yobeluise; Sukmaraga, Ayyub Anshari; Rahmadianto, Sultan Arif (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
Visual identity is the graphical representation of an entity, whether a product, brand, or individual, through various design elements crafted to create a cohesive and memorable visual image for the target audience. One element that can serve as a visual identity is a mascot, designed in alignment with the vision, mission, and unique characteristics of the company, in this case, Bintang Permata Sejati garment company. This study aims to strengthen the visual identity of Bintang Permata Sejati, a garment company, to enhance local brand awarness among the public, particulary in Pasuruan City, as well as to serve as a promotional tool for the company. Using qualitative methods such as interviews, surveys, and literature reviews, this research examines key visual elements, including the logo, typography, and color combinations, to express the brand’s values, messaging, and characteristics. The outcome of this study is the creation of a corporate mascot named Bipsy, which combines the forms of a rabbit and a turtle. The final deliverables include a Mascot Guide Book, along with primary 3D model assets of the Bipsy scharacter in .blend and .obj formats, complemented by supporting media such as figurine, character standees, knitted dolls, ID Cardes, lanyards, keychains, button pins, totebags, bucket hats, T-shirts, tumbler bottle, drawstring pouches, and mugs.